(untitled) (Jurnal Bahasa, 2001)
Lexicography is a knowledge related to the dictionary, which is one of the fields that need an application of linguistic theory. Meaning is the heart of a dictionary. When we speak about meaning, we are confined to the semantic and pragmatic discussions. The application of both disciplines offer a great help in solving the definition problems in general and the circularity of meaning in particular. The problems of circularity not only fail to provide the expected meaning but also cause tiresome to the dictionary users. The meaning given in the dictionary will always refer back to the same meaning given earlier. For instance, if a genus on beauty comprises a list of words- cantik, lawa, jelita, manis, anggun, tampon, segak has the feature of circularity- cantik means lawa, lawa means cantik, and so on, hence the users are not able to differentiate the degree of beauty in that domain. This article will show what is meant by circularity of meaning in detail, and attempts to posit how these problems can be solved with the semantic and pragmatic approach.